1964
DOI: 10.1098/rspb.1964.0001
|View full text |Cite
|
Sign up to set email alerts
|

The route of re-circulation of lymphocytes in the rat

Abstract: The experiments presented in this paper support the idea that the output of small lymphocytes from the thoracic duct of the rat (about 10 9 /day) is normally maintained by a large-scale re-circulation of cells from the blood to the lymph. It has been shown that the main channel from blood to lymph lies with in the lymph nodes and that small lymphocytes enter the nodes by crossing the walls of a specialized set of blood vessels, the post-capillary venules. In order to trace the fate of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
106
0

Year Published

1973
1973
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,132 publications
(112 citation statements)
references
References 20 publications
5
106
0
Order By: Relevance
“…HEVs were thought to be restricted to, and scattered throughout, the ''paracortex'' (Anderson and Anderson, 1975;Ford and Smith, 1982). It was and continues to be claimed that lymphocytes enter lymph nodes via HEVs only and at random (Gowans and Knight, 1964;Rouse et al, 1984). How these misconceptions arose will be examined in a later subsection.…”
Section: High Endothelial Venulesmentioning
confidence: 99%
See 1 more Smart Citation
“…HEVs were thought to be restricted to, and scattered throughout, the ''paracortex'' (Anderson and Anderson, 1975;Ford and Smith, 1982). It was and continues to be claimed that lymphocytes enter lymph nodes via HEVs only and at random (Gowans and Knight, 1964;Rouse et al, 1984). How these misconceptions arose will be examined in a later subsection.…”
Section: High Endothelial Venulesmentioning
confidence: 99%
“…Some of the most enduring misconceptions arose from the results of an intravenous transfer of labeled thoracic duct cells to determine whether lymphocytes re-circulate from blood to lymph (Gowans and Knight, 1964). At the organismal level, it was reported that labeled cells appeared to occur in equal concentrations in the various lymph nodes of the host, which was taken to indicate random entry.…”
Section: Origin Of Popular Conceptsmentioning
confidence: 99%
“…The development of thoracic duct cannulation in 1948 and availability of tritiated thymidine and adenosine allowed James Gowans to gain insight into lymphocyte function by tackling this, "Mystery of the disappearing lymphocytes" [5]. In a 1964 landmark study, it was demonstrated that small lymphocytes continuously re-circulate from the thoracic duct, to blood, through secondary lymphoid tissue, and back to the thoracic duct [6]. Understanding migration provided a critical foundation from which to study function.…”
Section: The Dark Agesmentioning
confidence: 99%
“…Most mature lymphocytes circulate systematically in the body in order to regulate the immune function appropriately [22,32]. This phenomenon suggests that there are some interactive mechanisms between lymphocytes and endothelial cell mediated tissue specific migrations.…”
Section: Lymphocyte Circulation and Cell Adhesion Molecules In The Immentioning
confidence: 99%